An evaluation of distller's grain price relationships and implications of increased ethanol production on grain processing practices in commercial feedlots - Van Winkle, Tyler W. (Kansas State University, 2008)
Very rapid growth in the ethanol industry has led to a void of information regarding price dynamics and utilization of distiller's grains. Understanding market conditions is essential for livestock producers to make informed decisions in the procurement of feedstuffs, especially as grain price levels have recently increased substantially. In this study, distiller's grain price discovery dynamics are evaluated to develop an understanding of spatial price relationships. The knowledge of price relationships reveals that users of distiller's grain should shop around when procuring the feedstuff. Additionally, because animal performance may be altered with increased inclusion of distiller's grains, regional competitive advantages could shift fed cattle production to geographic regions characterized by high of ethanol production plants. Therefore, the cost of current grain processing methods are evaluated to enhance the awareness of regional competitiveness and long term sustainability. The combination of these two objectives allows producers to better realize the implications of the ethanol industry on their ability to maintain their operations into the near future.
Keywords: Distiller's Grain; Price Discovery; Steam Flaking; Commercial Feedlots; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473)